1991
DOI: 10.1073/pnas.88.23.10797
|View full text |Cite
|
Sign up to set email alerts
|

A plausible model for reversal of neoplastic transformations in plants based on multiple steady states.

Abstract: We offer a plausible interpretation of some experiments on the reversal of neoplastic transformations in plants. We suggest that normal cells and tumorous cells represent multiple stable-steady states corresponding to a reaction feedback mechanism. The (autocatalytic) feedback loop is constructed from observations on the role played by myo-inositol: it increases the permeability of ions through the membrane and the biosynthetic pathway to myo-inositol is activated by ions. Provided that the permeabilities of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…the formation of organized structures such as roots or shoots, either spontaneously or after treatment with plant growth regulators. The regeneration of complete plants from a great number of habituated clones, as well as from fully transformed single-cell clones isolated from a young crown gall strain, has been presented as proof that both processes, habituation and Agrobacterium-transformation, are reversible Melchers, 1969, 1977;Hervagault et al, 1991;Syono and Fujita, 1994). The chimeric nature of a tumor, i.e.…”
Section: Plant Tumors Cancers and Inbetween Neoplastic Progressions mentioning
confidence: 98%
“…the formation of organized structures such as roots or shoots, either spontaneously or after treatment with plant growth regulators. The regeneration of complete plants from a great number of habituated clones, as well as from fully transformed single-cell clones isolated from a young crown gall strain, has been presented as proof that both processes, habituation and Agrobacterium-transformation, are reversible Melchers, 1969, 1977;Hervagault et al, 1991;Syono and Fujita, 1994). The chimeric nature of a tumor, i.e.…”
Section: Plant Tumors Cancers and Inbetween Neoplastic Progressions mentioning
confidence: 98%
“…Qui doute pour autant que par son degré d'abstrac-tion, une carte ou un plan est mieux à même de nous orienter que la multitude de signes contradictoires non pertinents que recèle la réalité concrète de l'environnement local ? Les modèles dynamiques dépassant le simple cadre des schémas à deux variables décrits plus haut sont aujourd'hui appliqués à l'interprétation d'un grand nombre de processus cellulaires, physiologiques et complexes, liés au developpement (cycle cellulaire [42], différenciation [43], morphogenèse [44]). Leur intérêt conceptuel reste en grande partie masqué aux expérimentateurs par l'exigence de réfutabilité que ceux-ci croient devoir leur appliquer.…”
Section: Attracteurs Multiples Et Immunitéunclassified
“…In such cases, the system can jump from one branch of (stable) steady states to the other but cannot undergo the reverse transition when the control parameter is varied across the bistability domain. The transition is therefore said to be irreversible. Moreover, the analysis of the conditions under which bistability occurs in the absence of hysteresis in simple theoretical models for chemical systems based on fully reversible kinetic has demonstrated that the phenomenon is not an artifact produced by approximations in the derivation of the evolution equations …”
Section: Introductionmentioning
confidence: 99%
“…The transition is therefore said to be irreversible. [15][16][17][18][19][20][21][22][23][24][25] Moreover, the analysis of the conditions under which bistability occurs in the absence of hysteresis in simple theoretical models for chemical systems based on fully reversible kinetic has demonstrated that the phenomenon is not an artifact produced by approximations in the derivation of the evolution equations. 26 In the present communication we consider the dynamic and steady-state behaviors of a multienzyme system arranged in three coupled substrate cycles and operating under thermodynamically open conditions by in-and outfluxes of substrate and products (CSTR).…”
Section: Introductionmentioning
confidence: 99%